2022
DOI: 10.1021/acs.organomet.1c00460
|View full text |Cite
|
Sign up to set email alerts
|

Mono and Dumbbell Silsesquioxane Cages as Dual-Response Fluorescent Chemosensors for Fluoride and Polycyclic Aromatic Hydrocarbons

Abstract: Pyrene-conjugated monomeric (2) and dimeric (5) shaped-silsesquioxane (SQ) cages, as chemical sensors for detecting fluoride and polycyclic aromatic hydrocarbons (PAHs), were prepared by Heck-coupling reactions between vinyl-functionalized SQ cages and bromo-substituted pyrenes. These sensors give a remarkable deep-blue fluorescence, which could be quenched in the presence of fluoride and electron-withdrawing PAHs. Interestingly, both sensors 2 and 5 show a rapid detection toward PAHs, while a high number of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…It is known that variations of the nature of alkaline metal ions strongly influence the structural features of phenylsurrounded CLMSs, especially in the context of supramolecular aggregation observed for large-sized ions (K, Rb, Cs) [ 16 , 23 , 25 , 47 , 60 ]. For the method of synthesis of methylsurrounded Cu-CLMSs, a universal approach that included alkaline hydrolysis [ 61 , 62 , 63 ] of MeSi(OMe) 3 assisted by the action of corresponding hydroxide MOH (M = Na, K, Rb, or Cs), was chosen. Then in situ formed alkaline metal siloxanolate [PhSi(O)OM] x species were brought into the exchange interaction with copper(II) chloride ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that variations of the nature of alkaline metal ions strongly influence the structural features of phenylsurrounded CLMSs, especially in the context of supramolecular aggregation observed for large-sized ions (K, Rb, Cs) [ 16 , 23 , 25 , 47 , 60 ]. For the method of synthesis of methylsurrounded Cu-CLMSs, a universal approach that included alkaline hydrolysis [ 61 , 62 , 63 ] of MeSi(OMe) 3 assisted by the action of corresponding hydroxide MOH (M = Na, K, Rb, or Cs), was chosen. Then in situ formed alkaline metal siloxanolate [PhSi(O)OM] x species were brought into the exchange interaction with copper(II) chloride ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…9,10 POSS has a cage-like structure, and is often used as a building block to modify materials' properties to achieve high surface area, fire-resistance, low heat conduction, inertness or even to increase the robustness of a material. [11][12][13] So far, the synthesis of silicone elastomers from the above mentioned materials has required several steps, the requirement of a template, fillers, and a long reaction time. [14][15][16][17][18] Herein, a superfast combination reaction between a cyclic tetrasiloxane and POSS can form a silicone elastomer via an anionic ring-opening polymerization.…”
mentioning
confidence: 99%
“…[17][18][19][20] As POSS molecules contain silicon atoms, they exhibit a unique affinity for fluoride anions and their functions such as fluoride encapsulation [21][22][23][24] and rearrangement reaction have been widely studied. 25,26 POSS derivatives have been also incorporated in several fluoride sensors for their chemical and thermal stability and versatile molecular designs towards various detection modes such as turn-on 27 and turn-off responses 28,29 and color changes. [30][31][32][33][34] In these studies, decomposition of the POSS nanocage by fluoride anions is a key step.…”
mentioning
confidence: 99%
“…From the integration ratio of the signal peak from the triplet amide proton (8.81 ppm), it was confirmed that eight C343 units can be covalently attached to the POSS moiety. The signal at À66.9 ppm in the 29 Si NMR spectrum indicates that the cubic T8 POSS cage should remain intact (Fig. S3, ESI †).…”
mentioning
confidence: 99%
See 1 more Smart Citation